The interaction of heparin tetrasaccharides with chemokine CCL5 is modulated by sulfation pattern and pH - Singh, A.; Kett, W.; Severin, I.; Agyekum, I.; Duan, J.; Amster, I.; Proudfoot, A.; Coombe, Deidre; Woods, R. (American Society for Biochemistry and Molecular Biology Inc., 2015)
© 2015 by The American Society for Biochemistry and Molecular Biology, Inc. Interactions between chemokines such as CCL5 and glycosaminoglycans (GAGs) are essential for creating haptotactic gradients to guide the migration of leukocytes into inflammatory sites, and the GAGs that interact with CCL5 with the highest affinity are heparan sulfates/heparin. The interaction between CCL5 and its receptor on monocytes, CCR1, is mediated through residues Arg-17 and -47 in CCL5, which overlap with the GAG-binding 44RKNR47 "BBXB" motifs. Here we report that heparin and tetrasaccharide fragments of heparin are able to inhibit CCL5-CCR1 binding, with IC50 values showing strong dependence on the pattern and extent of sulfation. Modeling of the CCL5-tetrasaccharide complexes suggested that interactions between specific sulfate and carboxylate groups of heparin and residues Arg-17 and -47 of the protein are essential for strong inhibition; tetrasaccharides lacking the specific sulfation pattern were found to preferentially bind CCL5 in positions less favorable for inhibition of the interaction with CCR1. Simulations of a 12-mer heparin fragment bound to CCL5 indicated that the oligosaccharide preferred to interact simultaneously with both 44RKNR47 motifs in the CCL5 homodimer and engaged residues Arg-47 and -17 from both chains. Direct engagement of these residues by the longer heparin oligosaccharide provides a rationalization for its effectiveness as an inhibitor of CCL5-CCR1 interaction. In this mode, histidine (His-23) may contribute to CCL5-GAG interactions when the pH drops just below neutral, as occurs during inflammation. Additionally, an examination of the contribution of pH to modulating CCL5-heparin interactions suggested a need for careful interpretation of experimental results when experiments are performed under non-physiological conditions.